Microsecond dark-exciton valley polarization memory in two-dimensional heterostructures - Chongyun Jiang (Nature Portfolio, 2018)
Owing to their valley degree of freedom, atomically thin transition metal dichalcogenides show promise for valleytronics. Here, the authors leverage the dark excitons of two-dimensional van der Waals heterostructures to demonstrate a microsecond valley polarization memory effect.